Perancangan Sistem Informasi Pariwisata dan Kebudayaan Kabupaten Maybrat Berbasis WEB (Studi Kasus : Komunitas Pencinta Alam Papua Barat) - Manuhutu, Melda Agnes; Flasao, Yulianti; Uktolseja, Lulu Jola (Fakultas Teknik, Universitas Tadulako, 2018)
Accompanied by the development of information technology, communication technology has developed rapidly. One sector that is developing in the field of tourism which contributes to more interactive information through the internet. Where Maybrat Regency has considerable tourism and cultural potential, it is managed by the Maybrat Regency Tourism and Culture Community which is very useful if managed well and effectively. This is to improve the economy of the community, the quality of human resources, through tourism assistance that enables increased regional pride. Accurate presentation of the area that can be used to increase revenue in the region itself. Now there is not enough information about tourist objects in Maybrat Regency so that not many tourists and people know the potential of tourism objects. The system development model used is the prototype model. By building interfaces using Adobe Dreamweaver CS6. The database is stored using php and displayed via XAMMP. This system is also built on the framework of a system that is a code igniter.